2006
DOI: 10.1007/s00376-006-0002-9
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the storm-induced SST cooling on hurricane intensity

Abstract: The effects of storm-induced sea surface temperature (SST) cooling on hurricane intensity are investigated using a 5-day cloud-resolving simulation of Hurricane Bonnie (1998). Two sensitivity simulations are performed in which the storm-induced cooling is either ignored or shifted close to the modeled storm track. Results show marked sensitivity of the model-simulated storm intensity to the magnitude and relative position with respect to the hurricane track. It is shown that incorporation of the storm-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 31 publications
2
43
0
Order By: Relevance
“…3c), while the post-storm SST is cooler than the average SST. The difference between the SST prior to and after the storm is related to the storm intensity (Zhu and Zhang 2006). The stronger the tropical cyclone/hurricane, the larger the difference is found.…”
Section: Resultsmentioning
confidence: 97%
“…3c), while the post-storm SST is cooler than the average SST. The difference between the SST prior to and after the storm is related to the storm intensity (Zhu and Zhang 2006). The stronger the tropical cyclone/hurricane, the larger the difference is found.…”
Section: Resultsmentioning
confidence: 97%
“…First, TC's maximum surface wind speed V max values and sea-air temperature contrast (SAT) show a distinct correlation in their variabilities (cf., [32]). Second, SST and air temperature values are linearly related to a first order approximation [33,34] and thus SST and SAT (SST minus air temperature) too are correlated.…”
Section: Methodsmentioning
confidence: 99%
“…On the first assumption, the time-evolution of V max and SAT has been shown to be identical in their directions (not amplitude) during phases of intense storms (cf., [32]) due to enhanced vertical transport. (An offline analysis also showed significant spatial linear correlation with sea-air temperature contrast.).…”
Section: Development Of a Linear V Max Model And Its Validation Againmentioning
confidence: 99%
“…Previous studies have shown that TC intensity is significantly affected by the vertical structure of warm ocean eddies [12,22] and SST [69][70][71][72][73]. However, it is not clear to what extent the vertical structure of warm ocean eddies affects TC intensity, mainly due to the lack of in situ measurement data of the vertical structure of warm ocean eddies.…”
Section: Influences Of Sst On Tc Intensity Changementioning
confidence: 99%